PENERAPAN FAMILY THERAPY DAN LOGO THERAPY TERHADAP SELF ESTEEM PENYANDANG DISABILITAS TUBUH - Hattu, Maxmillian Roberth (Sekolah Tinggi Kesejahteraan Sosial (STKS) Bandung, 2016)
Abstract Self-esteem refers to the belief Disability possessed skills, appreciation of others, their competence, responsibility to self and family responsibilities even others. The purpose of this study was to examine about self esteem of persons with body disabilities through family therapy and logo therapy. If the self-esteem of persons with body disabilities, They are can actualize themselves well, and goodwell social functioning. This study has the benefit, both theoretically and practically to thedevelopment of social work.The method used in the research is Action Research. The data collection techniques used are in-depth interviews, participant observation and documentation study. The subjects in this reseach is